Representing the representers: Non-Western depictions of Orientalists and Orientalism in Turkish, Mexican, and Bengali writing. (March 2023) - Almond, Ian
How do writers from regions with a historical experience of colonialism depict Western Orientalists in their work? What exactly does it mean to "reverse the gaze" and include the Orientalist within the frame of representation? The article considers the non-Western representation of Orientalists and Orientalism in literary texts from three different regions (Turkey, Mexico, and Bengal), concentrating in particular on Oguz Atay's Tutunamayanlar (The Disconnected), Ignacio Padilla's Antipodes, and Amitav Ghosh's In an Antique Land, but also referring to a wide selection of other texts in the process. It suggests three categories of such representation — parodic, empathetic, and authoritative, in ascending order of sympathy — and proposes, in the analysis of the various fictitious representations of Orientalists examined, a central link between Orientalism and the sacred. Finally, the question of the ironic representation of Orientalists — the extent to which a redemptive irony is adopted by structures of power as a tool of self-preservation — is also considered.